Peran Parachurch dalam Pertumbuhan Iman Jemaat Gereja Lokal: Sebuah Pendekatan Ekklesiologis - Saputra, Gilbeth Pramana (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
The local church in the contemporary context faces various complex challenges, including limitations in human resources, highly specialized ministry programs, and increasingly diverse capacity-building needs. In response to these demands, parachurch organizations have developed to fill ministry gaps that cannot yet be optimally addressed by local churches. However, the presence of parachurch organizations often creates tension with local churches due to perceptions of competition and functional overlap that may potentially divide the unity of the body of Christ. This study aims to analyze the role of parachurch organizations in supporting the faith growth of local church congregations through a theological-ecclesiological approach. The research employs a qualitative methodology with a systematic literature review, involving analyses of systematic theology, ecclesiology literature, and case studies of church-parachurch collaborations across various denominations. The analysis is conducted using a Reformed theological framework and a holistic ecclesiological perspective. The findings indicate that parachurch organizations have a significant complementary role in the spiritual growth of congregations through three main functions: deep specialization in ministry, mobilization of cross-denominational resources, and innovation in faith development programs. An effective collaboration model can be achieved through the principle of subsidiarity, whereby parachurch organizations assume specific roles that cannot be optimally performed by the local church, while still honoring the pastoral authority and ecclesiological structure of the local church. This study contributes to the development of a practical ecclesiological model that integrates the role of parachurch organizations as strategic partners of the local church. Collaborations grounded in solid theological foundations can optimize the faith growth of congregations without compromising the unity and ecclesiological integrity of the local church.